2015
DOI: 10.1177/0271121414566014
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Children With Special Needs in Early Childhood Education

Abstract: Whereas the inclusion of children with special needs in regular classrooms has gained increasing advocacy, teachers’ attitudes vary. Previous studies examining teacher attitudes have focused on primary and secondary schools in the Western world, and little is known about early childhood settings in Eastern countries. This study used MANOVA to examine preschool teachers’ attitudes in Hong Kong (N = 410). Teachers reported only modest support for inclusion. Teachers with training in special education were strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 48 publications
2
38
0
7
Order By: Relevance
“…This is consistent with Sproston et al (2017); although one autistic girl cautions against unrealistic expectations. Teachers hold a variety of attitudes to the inclusion of autistic young people in mainstream schools, with several writers describing teachers attitudes as influential in the inclusion of autistic young people (see Glazzard, 2011;Lee, Young, Tracey, & Barker, 2015;McGregor & Campbell, 2001).…”
Section: What Experiences Have Autistic Young People Had During Theirmentioning
confidence: 99%
“…This is consistent with Sproston et al (2017); although one autistic girl cautions against unrealistic expectations. Teachers hold a variety of attitudes to the inclusion of autistic young people in mainstream schools, with several writers describing teachers attitudes as influential in the inclusion of autistic young people (see Glazzard, 2011;Lee, Young, Tracey, & Barker, 2015;McGregor & Campbell, 2001).…”
Section: What Experiences Have Autistic Young People Had During Theirmentioning
confidence: 99%
“…An inclusive educational classroom refers to a learning environment where the academic, physical, and social needs of all learners, including those with disabilities, are addressed within one comprehensive setting [1,2]. The practice of inclusive education-or inclusion-within general education classrooms is becoming more prevalent within early childhood settings [3][4][5]. With this increase in practice, early childhood educators routinely encounter and teach students who have a range of special needs within regular classroom settings; however, parents of children served within these inclusive settings report that quality of inclusion can vary greatly among schools and individual service providers within school settings [1].…”
Section: Introductionmentioning
confidence: 99%
“…Children with disabilities are entitled to the same educational experiences as their peers without disabilities [7]. While this is the law in the United States, the practice of inclusion is expanding to more countries throughout the world [5,8]. This expansion of services is due, in part, to documented benefits of inclusive classrooms where students with disabilities are making greater gains in academic skills and behavioral characteristics than same-age peers who receive services in special schools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, training and awareness-raising in the educational community are essential to the development of positive attitudes. As noted in other research, it was observed that all the participants see teachers as a key factor in the inclusive education process (Arnaiz & Azorín, 2014;Lee, Yeung, Yeung, Tracey, & Barker, 2015). Teachers are directly responsible for facilitating the learning process (Montilha, Temporini, Nobre, Gasparetto, & José, 2009).…”
Section: Coordinationmentioning
confidence: 77%